Strategi Mengatasi Tantangan Mengimplementasikan Proses Uji Coba Terbatas dalam Penelitian Tindakan Kelas - Rida Restu Restalillah (Cipta Media Harmoni, 2025)
Challenges encountered when implementing a limited trial process can complicate the success of Classroom Action Research. The purpose of this study was to identify appropriate strategies for overcoming the challenges of implementing a limited trial process in Classroom Action Research. The method used was a literature review to collect and analyze data from previous studies related to the topic of strategies for overcoming challenges in implementing a limited trial process in Classroom Action Research. The results showed that to overcome the challenges in implementing a limited trial in Classroom Action Research, teachers need to plan carefully, utilize technology, use resources efficiently, and actively involve students and conduct evaluations to improve the quality of implementation. These results imply that teachers need to plan carefully, utilize technology, manage resources, and involve students to overcome the challenges in implementing a limited trial process in Classroom Action Research.